Poetic structure and structure of love : A PHONOLOGICAL APPROACH TO A SHAKESPEAREAN SONNET (Journal of the College of Basic Education, 2022)
This study proceeds on the hypothesis that the sound patterns of apoem contribute a great deal to build the poet's world — view .The study isan attempt to investigate the texture of sound in Shakespeare's sonnet (55), " Not marble , nor gilded monuments " . The sonnet will be approachedas a phonological unit of meaning. The study falls into three parts . Part Iintroduces the key concepts of modern phonetics and phonology . Attentionis drawn to the phonological aspect of the verse structure by showing the "stress-producing pulses " and the " syllable — producing pulses" whicheither of the processes exists in nearly all human languages . Part II dealswith the phonological mechanisms which create the poem as an aestheticform . Of these mechanisms are the widely known sound devices such as , "rhythm", " rhyme " , " alliteration " , " onomatopoeia " and so on . Theseterms will be looked at from a _ phonological perspective.Shakespeare's sonnet will be investigated in terms of Cummings andSimmons's " Systemic Description "in its phonological aspect . Theanalytic mode will show how the language operates to produce the poem asa linguistic and aesthetic form.